Custom ocular prosthetic rehabilitation in patient with Post-enucleation deep eye socket using iris button technique - Lisda Damayanti; Nathania (Indonesia Prosthodontic Association, 2025)
The eyes are a vital component of facial esthetics and expression. Ocular defects can have a significant psychological impact on patients. An ocular prosthesis is an artificial maxillofacial prosthesis used to restore the appearance of a missing eye. It can be customized to replicate the patient’s natural eye in terms of color, shape, size, and movement, resulting in a realistic and natural-looking outcome. The objective of this case report is to explain the procedural steps involved in the fabrication of a custom ocular prosthesis, employing an impression technique using a custom tray and incorporationg the iris button technique. A 36 years old female patient came to RSGM Padjadjaran University to fabricate a new eye prosthesis. The patient had a prior medical history of a severe ocular infection, which necessitated enucleation surgery. The ocular prosthesis was fabricated using an impression technique with a custom tray, employing a physiological impression method to capture the deep regions of the superior palpebral socket. The sclera, iris, and pupil were fabricated using the iris button technique. Custom ocular prostheses incorporating physiological impression technique and iris button technique offer ocular prosthesis with good stability and more natural appearance. Keywords: custom ocular prosthesis, physiologic impression, iris button